2014
DOI: 10.1111/dme.12601
|View full text |Cite
|
Sign up to set email alerts
|

A pregnancy lifestyle intervention to prevent gestational diabetes risk factors in overweight Hispanic women: a feasibility randomized controlled trial

Abstract: AIMS: To pilot the feasibility of a prenatal lifestyle intervention to modify physical activity and diet among pregnant overweight and obese Hispanic women, with the aim of reducing risk factors for gestational diabetes mellitus. METHODS: Women were randomized either to a lifestyle intervention (n = 33, 48.5%), consisting of a culturally and linguistically modified, motivationally targeted, individually tailored 6-month prenatal programme, or to standard care (n = 35, 51.5%). Bilingual and bicultural health ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(104 citation statements)
references
References 33 publications
1
100
1
2
Order By: Relevance
“…67686970717273747576777879808182838485868788 A further 45 trials (9945 women)8990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122123124125126127128129130131132133 were identified after the IPD acquisition timeline until February 2017.…”
Section: Resultsmentioning
confidence: 99%
“…67686970717273747576777879808182838485868788 A further 45 trials (9945 women)8990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122123124125126127128129130131132133 were identified after the IPD acquisition timeline until February 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, two were RCTs that included exercise only 57 60. One study included women with obesity prior to pregnancy,57 and the other included women at high risk of developing GDM 60. In both studies, glycaemic control was not different between the exercise and control groups postintervention.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies and review articles over the past 10-15 years ( 129 , 130 ) have suggested that women who routinely participate in exercise during pregnancy have better glucose control (among women with gestational diabetes mellitus) ( 31 ), have less GWG ( 91 , 120 ), have less postpartum weight retention ( 91 ), and give birth to infants that are smaller (but within the normal weight range) than those who do not exercise ( 61 ). Hawkins et al ( 56 ) have demonstrated the benefits of a clinically feasible exercise intervention in diverse populations. Mourtakos et al ( 92 ) found that moderate PA during pregnancy, as well as GWG and smoking status, were significantly associated with offspring obesity at age 8 years.…”
Section: Prenatal Influences On Early Life Obesitymentioning
confidence: 99%